Energy Statistics Compilers' Manual - United Nations Department of Economic; Social Affairs (United Nations, 2022)
The Energy Statistics Compilers Manual (ESCM) is a publication that complements in a practical manner the International Recommendations for Energy Statistics (IRES), which provides a comprehensive methodological framework for the collection, compilation and dissemination of energy statistics in all countries irrespective of the level of development of their statistical system. In particular, IRES provides of a set of internationally agreed recommendations covering all aspects of the statistical production process, from the institutional and legal framework, basic concepts, definitions and classifications to data sources, data compilation strategies, energy balances, data quality issues and statistical dissemination. The ESCM is written primarily for practitioners that are tasked with building up or improving the energy statistics programme of a country or institution in a way that is consistent with the latest international standards and produces reliable and internationally comparable data.The ESCM aims to assist countries in the collection, analysis and dissemination of energy statistics to international standards. Its purpose is to complement IRES by providing explanations that make it easier to apply the principles defined in IRES in practical applications, to understand specific relationships that facilitate or complicate the adaptation of such principles to national situations and therefore provide practical ways to implement an energy statistics programme that is consistent with the established international recommendations.